Organizational Context and Healthcare Reforms: What Effect on the Professional Distress of Canadian Social Workers and Social Service Provision? - Lévesque, Maude; Negura, Lilian (Frontiers in Sociology, 2021)
This study examined the lived experience of Canadian clinical social workers in light of the organizational context in which they work. The literature indicates an alarming rise of occupational psychological distress in social workers, which aligns with the rise of the neoliberal ideology within the Canadian healthcare sector. While we know that organizational constraints and structural reforms affect social worker’s workplace well-being, it remains unclear how these changes are represented by front-line practitioners and how they affect the provision of social services in healthcare settings. To deepen our understanding of this issue, we conducted a thematic analysis of thirty semi-directed interviews with social workers currently practicing in three Canadian cities (Ottawa, Moncton and Winnipeg). Discussions of daily work life, responsibilities, autonomy and subjective understandings of the social worker’s role revealed which organizational constraints were the most significant in everyday practice and how they relate to their professional identity and mandate. Provincial healthcare reforms were generally found to have negative effects on clinical social workers, whose struggles for recognition were impaired by the fundamentally neoliberal ideologies behind the large-scale restructuring of service provision, themselves at odds with the humanistic principles of social work. Our findings further suggest that structural changes under the New Public Management frame could be detrimental to both the quality of services provided by clinical social workers and their well-being. Overall, this investigation highlights the importance of organizational improvements in the workplace through systemic changes that would concurrently target managerial expectations, resources allocation, autonomy, work-life balance and respect for professional values.